OSTEOSARCOMA HAS NOT BECOME ATTENTION TO SOCIETY PROFILE OF OSTEOSARCOMA PATIENTS AT DR. SOETOMO GENERAL HOSPITAL SURABAYA “A RETROSPECTIVE STUDY” - Ferdiansyah Mahyudin; Mouli Edward; Muhammad Hardian Basuki; Yunus Abdul Bari; Yesa Suwandani (Universitas Airlangga, 2018)
Background: Osteosarcoma is the most common bone neoplasm found in the community but evaluation osteosarcoma cases in RSUD Dr. Soetomo has not been updated since 1995.Purpose: This study o osteosarcoma patient characteristic as well as therapy at Dr. Soetomo General Hospital in 2007 to 2016. It expects to show survival rates of osteosarcoma patient, so it can be a reference for searching the problems in the treatment of osteosarcoma cases and helps to decide treatment for osteosarcoma.Research Methods: Descriptive retrospective study, conducted on osteosarcoma patients at Dr. Soetomo General Hospital during 2007-2016 periods. Data were obtained from Ortho tumor patient database, and contacting them by phone or home visit.Results: Osteosarcoma patients was found mostly in 2015, while the least in 2008, with trend increasing by time. Majority of the patients came with advanced stage. Osteosarcoma treated mostly by amputation, either with or without chemotherapy. The survival rate in the first, second, or the fifth year was found lower than other references. Most common cause of mortality was the metastasis.Conclusion: Awareness of the society about the cancer sign of cancer and desire to use medical treatment as a priority is still low. This causes a low early detection rate of osteosarcoma and a high rate of metastatic cases because of inappropriate early treatment. Further socialization and increased awareness of medics about the suspicion of osteosarcoma are needed to improve the success rate of treatment as well as the survival rate.